Kif2 localizes to a subdomain of cortical endoplasmic reticulum that drives asymmetric spindle position. Issue 1 (December 2017) - Costache, Vlad; Hebras, Celine; Pruliere, Gerard; Besnardeau, Lydia; Failla, Margaux; Copley, Richard; Burgess, David; Chenevert, Janet; McDougall, Alex
Abstract Asymmetric positioning of the mitotic spindle is a fundamental process responsible for creating sibling cell size asymmetry; however, how the cortex causes the depolymerization of astral microtubules during asymmetric spindle positioning has remained elusive. Early ascidian embryos possess a large cortical subdomain of endoplasmic reticulum (ER) that causes asymmetric spindle positioning driving unequal cell division. Here we show that the microtubule depolymerase Kif2 localizes to this subdomain of cortical ER. Rapid live-cell imaging reveals that microtubules are less abundant in the subdomain of cortical ER. Inhibition of Kif2 function prevents the development of mitotic aster asymmetry and spindle pole movement towards the subdomain of cortical ER, whereas locally increasing microtubule depolymerization causes exaggerated asymmetric spindle positioning. This study shows that the microtubule depolymerase Kif2 is localized to a cortical subdomain of endoplasmic reticulum that is involved in asymmetric spindle positioning during unequal cell division. Early ascidian embryos have a cortical subdomain of endoplasmic reticulum (ER) that controls asymmetric spindle positioning driving unequal cell division. Here the authors show that the microtubule depolymerase Kif2 is localized to a cortical subdomain of the ER that is involved in asymmetric spindle positioning.